2019
DOI: 10.1108/ajems-01-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and compliance with feed quality standards: the case of chicken feeds in Tanzania

Abstract: Purpose The purpose of this paper is to examine the determinants of awareness of and compliance with chicken feed standards among chicken farmers in Tanzania. Design/methodology/approach A total of 107 respondents in two regions were selected through simple random sampling. Structured questionnaires were used to collect data. Descriptive statistics and multiple regression approaches were used in data analysis. Findings The results revealed that the level of awareness of standards is low and the compliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…One overarching strategy is education and information provision, which in this study largely involves extension services. This is consistent with what other agricultural regulatory compliance scholars have found regarding extension service and compliance (see for example, Longo et al, 2019;Muriithi et al, 2011). Longo and fellow researchers reported that extension services were significantly correlated with compliance with chicken feed standards in Tanzania.…”
Section: Discussion and Policy Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…One overarching strategy is education and information provision, which in this study largely involves extension services. This is consistent with what other agricultural regulatory compliance scholars have found regarding extension service and compliance (see for example, Longo et al, 2019;Muriithi et al, 2011). Longo and fellow researchers reported that extension services were significantly correlated with compliance with chicken feed standards in Tanzania.…”
Section: Discussion and Policy Implicationssupporting
confidence: 88%
“…Other normative factors that have been found to influence agricultural regulatory compliance are education, information provision and extension services for farmers (Longo, Akyoo, & Sørensen, 2019;Muriithi et al, 2011). Longo et al (2019) examined awareness and compliance with feed quality standards among 107 chicken farmers in Tanzania and found that compliance was significantly related to access to extension services, the health consciousness of farmers, and farmers' awareness of the law. In Kenya, Muriithi et al (2011) investigated the determinants of awareness and compliance with European food safety standards among bean producers.…”
Section: Determinants Of Compliance By Farmersmentioning
confidence: 99%
See 1 more Smart Citation
“…In a move seen as tit-for-tat, Kenya banned Tanzania's tourist vehicles from fetching or dropping passengers from its airports (The Standard, 2015). In October 2017, the government of Tanzania was reported to have burnt 6400 live chicks from Kenya, alleging that they were illegally smuggled into its territory (Longo, Akyoo & Sørensen, 2019). A similar move was witnessed in February 2018 when Magufuli's government confiscated 5000 live chicks (Longo, Akyoo & Sørensen, 2019).…”
Section: Past Differences and The Widening Cracksmentioning
confidence: 97%
“…In October 2017, the government of Tanzania was reported to have burnt 6400 live chicks from Kenya, alleging that they were illegally smuggled into its territory (Longo, Akyoo & Sørensen, 2019). A similar move was witnessed in February 2018 when Magufuli's government confiscated 5000 live chicks (Longo, Akyoo & Sørensen, 2019). Similarly, Tanzania's authority auctioned over 1000 cattle belonging to Kenyan herders.…”
Section: Past Differences and The Widening Cracksmentioning
confidence: 98%